Trees in the ground or in pots: between theory and practice in Poland and Ukraine - Mizgajski, Andrzej; Trzaskowska, Ewa; Dubis, Lidiya; Zajaczkowski, Dominik (Bulletin of Geography. Socio-economic Series, 2025)
Rules for planting trees in historical areas and associated challenges have been considered. We analysed policy documents and opinions of officials responsible for managing greenery. With exceptions, trees are planted in both private and public spaces in the considered cities, while potted specimens are found in public spaces. Local policy documents refer to improving urban living conditions without specific operational directives on cultural, environmental, social and technical conditions for new plantings. Officials have identified technical problems such as a lack of biologically active spaces, difficulties in locating new trees due to existing underground infrastructure, and the lack of space for large pots due to the narrowness of streets. Urban greenery in Polish cities is managed by a variety of agencies, which is a significant inconvenience. Lviv in Ukraine is the only studied city with a cohesive program and centralized management under one department.